The application of range of motion (ROM) and coordination on volleyball spike - Liu, L.-F.; Liu, G.-C.; Sue, C.-W.; Huang, C. F. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to investigate the suitable timing and coordination of body segments during volleyball spike, and find the critical concepts applied on spikinglearning in the air. Cinematography (250 frame/sec, sagittle plane) was used in this study, and Kwon 3D software was used to analyze the timing and coordination of arm swing motion in the air among top and second level female volleyball athletes. The results of this study as following: 1. Enough range of motion (ROM) before ball hitting is the main factor of spiking technique; 2. Proper time-distribution of back-swing, turn-swing and forward-swing cause the proper time of ball hitting. The conclusion of spiking technique was described as following hint concepts: 1. "lead": leading back swing at the beginning of takeoff, 2. "pull": back swing by pull of elbow and wrist, simultaneously. 3. "turn": make a enough ROM of swing phase. 4. "up": during up, 5. "hit":hitting ball by arm and body momentum.